Simplify 18 - 2[x (x - 5)].

Question

Asked 11/13/2014 2:12:32 PM

Updated 11/13/2014 6:33:35 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [11/13/2014 6:33:35 PM]

s

= x^2 + 3x - 4x - 12

= x^2 - x - 12

smp0784|Points 4142|

= -(7 - 3)

= -7 + 3

= -4

a_dgzmn|Points 96|

-3(-1)^3 - 4(-1);

-3(-1) - (-4);

3 + 4;

= 7

jeifunk|Points 36717|

smp0784|Points 4142|

Question

Asked 11/13/2014 2:12:32 PM

Updated 11/13/2014 6:33:35 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [11/13/2014 6:33:35 PM]

Rating

5

18 - 2[x (x - 5)]

= 18 - 2(x^2 - 5x)

= 18 - 2x^2 + 10x

= 18 - 2(x^2 - 5x)

= 18 - 2x^2 + 10x

Added 11/13/2014 6:27:36 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/14/2014 8:19:19 AM]

5

The thirtieth term of the following sequence:-6, -4, -2, 0, ... is 52 .

Common difference = 0 -(-2) = -2 - (-4) = -4 - (-6) = 2

30th term = -6 + (30 - 1)*2 = -6 + 58 = 52

Common difference = 0 -(-2) = -2 - (-4) = -4 - (-6) = 2

30th term = -6 + (30 - 1)*2 = -6 + 58 = 52

Added 11/13/2014 6:32:43 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/14/2014 8:21:51 AM]

5

ab - c = 9

c = ab - 9

The solution for c is ab - 9 .

c = ab - 9

The solution for c is ab - 9 .

Added 11/13/2014 6:33:31 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/14/2014 8:22:34 AM]

34,464,328

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 804 [Total 6677] Ratings 19 Comments 614 Invitations 0 Offline

There are no comments.